Formulasi Sediaan Gel Dari Ekstrak Etanol Herba Pegagan (Centella asiatica (L) Urb) - Nurlatifah Nurlatifah; Lidyawati Lidyawati; Rosa Mardiana; Dwi Putri Rejeki; Mona Asiah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Indonesia is a rich country in terms of flora and fauna diversity. Indonesia's wealth with various types of flora is a highlight for science, one of which is the gotu kola herb (Centella asiatica (L) Urb). The chemical compound asiaticoside is part of the triperoids contained in the gotu kola herb which has the potential as antibacterial, antifungal, antioxidant and anti-cellulite on the skin, suitable for topical preparations such as gels. This study aims to formulate a gel preparation from the ethanolic extract of the gotu kola herb (Centella asiatica (L) Urb) which meets the requirements of a good gel. The formulation of the gel preparation was carried out with concentrations of 20%, 25%, and 30%. Extracted by maceration method using 70% ethanol and in a vacuum rotary evaporator to obtain a thick extract. Evaluation of the gel preparation was carried out by organoleptic test, homogeneity test, pH test, dispersibility test, adhesion test and irritation test. The results of the evaluation carried out with the three concentrations met the requirements of the organoleptic test, homogeneity test, pH test, adhesion test and irritation test, but the ethanol extract gel of the gotu kola herb at concentrations of 20%, 25% and 30% did not meet the requirements for the good dispersion test